The Consumerization of Financial Regulation - Helen A. Garten (Washington University Law Quarterly, 1999)
Part I shows how consumer protection is becoming the leading rationale for financial regulation. Part II argues that the consumerization of financial regulation may distort analysis of the costs and benefits of regulation, leading to the inefficient production of regulation. Part III assesses the effect of the consumerization of regulation on the regulators themselves.
Keywords: Consumer protection; Financial services industry; Banking industry; Banking law; Deregulation; Financial institutions; Financial services; Securities law